Organic-inorganic PTAA-SiGe transparent optical materials performancem analysis for photo device applications - Nasir, Syafiqa; Bablu Kumar Ghosh, Bablu Kumar Ghosh; Pratap Kumar Dakua, Pratap Kumar Dakua; Fuei Pien Chee, Fuei Pien Chee; K.A. Mohamad, K.A. Mohamad; Saad, Ismail (Elsevier, 2024)
The SiGe materials has currently received a lot of interest due to its application for the advancement of optoelectronics and related sensor technologies. Its promising stability, and band gap-dependent performance for both bulk and nano-crystalline properties are vital as optical materials. To investigate the electrical performance of SiGe active materials based photo device, the spin coated organic p-materials contact is developed on sputtered SiGe on Quartz and ITO glass substrates. Both Si0.8Ge0.2 and Si0.9Ge0.1 films greater than 85 % visible band transparency are predicted that the deposited SiGe is nano-crystalline nature. It is also revealed from absorption-based band gap, AFM grain size and XRD analysis. The transmittance of SiGe thin film is increased with the microstrain of the films as a result, better opto-electrical performance is displayed. Ge composition though slightly makes variation of lattice constant and strain effect however, relatively lower transmittance films greater current density is exhibited. A higher rectifying ratio for lower transparent SiGe material deposited on ITO glass substrate is shown in the dark. Transparency and optoelectrical performance viewpoint white light illuminated PTAA/Si0.8Ge0.2 is shown better on Quartz substrate whereas the dark analysis PTAA/Si0.9Ge0.1 is realized more favorable on ITO glass substrate.